The Increasing Use and Abuse of Tapentadol and Its Incorporation Into a Validated Quantitative Method. Issue 7 (18th April 2018) - Partridge, Emma; Teoh, Eric; Nash, Christine; Scott, Timothy; Charlwood, Cheryl; Kostakis, Chris
Abstract: Tapentadol is a centrally acting synthetic analgesic which is prescribed for the treatment of a range of chronic pain conditions. Its use in treating various pain conditions is increasing and, as with other opioids, it has the potential to be abused. We describe a three-stage incorporation of tapentadol into validated screening and quantitative methods through: (i) addition of retention time/mass spectral data to a database, (ii) qualitative validation and (iii) quantitative validation. This represents an efficient and flexible approach to the incorporation of new compounds of interest to existing screening methods. Tapentadol was analyzed in blood and serum samples using alkaline liquid–liquid extraction with identification and quantitation by liquid chromatography/time-of-flight mass spectrometry. In a series of six post-mortem cases where tapentadol was detected but was not a primary causative factor in death, blood concentrations ranged from 0.01 to 1.0 mg/L. In two cases where tapentadol was a significant contributor to death, post-mortem blood concentrations were 1.7 and 3.9 mg/L. In one of these fatal cases, ante-mortem blood and serum were also analyzed. The tapentadol concentration in the post-mortem blood was 30% higher than in the ante-mortem blood after a post-mortem interval of 13 days, indicating some potential for post-mortem redistribution. The measured ante-mortem blood:serum ratio was 1.7, and is the first such ratio to be reported. Other drugs were detected in almost all cases, with the majority being prescription analgesics, sedatives and antidepressants. The number of cases in which tapentadol has been detected has increased in recent years, highlighting the importance of screening for this drug in forensic toxicological laboratories.